Komunikasi Publik Dalam Upaya Mendukung Kebijakan Pemerintah Di Saat Pandemi Covid-19 - Aat Ruchiat Nugraha; Evi Novianti; Diah Fatma Sjoraida; Ade Kadarisman; Aang koswara (Jurnal SOLMA, 2021)
Indonesia, as a country fighting Covid-19 attacks, needs to gain comprehensive knowledge for all its citizens to be able to get out of times of health crisis in. One solution that needs to be communicated in the face of this virus outbreak is a healthy lifestyle according to the advice of health protocols issued by the WHO and Indonesian government authorities. Through community service activities (PPM) integrated with KKN Mahasiswa (KKNM) Universitas Padjadjaran during this pandemic, we strive to contribute optimally in various socialization and education activities regarding the handling of Covid-19. This method of implementation of PPM - KKNM is carried out using online and offline modes in each residence of KKNM students. The results show that public communication about healthy lifestyles in the pandemic era based on the utilization of social media can be a means of educating continuously about the handling of Covid-19. The conclusion of the activity shows that through the approach of public communication conducted offline and online can provide knowledge and understanding about the efforts of handling Covid-19. The advice is that synergy needs to be done in the management of public communication that implements various communication channels to gain the full and consistent public trust of the target audience.